ANALISIS DAN STRATEGI PROBLEM SOLVING PADA PERILAKU BULLYING DI UPTD SD NEGERI 122348 DAN SD SWASTA TAMAN ASUHAN PEMATANGSIANTAR - Simanjuntak, Melvin; Julveri Manasar; Mia Afani; Sapna Arya Dita Saragih; Thesa Saragih; Ica Fitri Tanjung; Shelvia Distini Silalahi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses a case study of bullying behavior in elementary schools. Bullying can have a negative impact on victims, and this research uses a descriptive qualitative approach to describe this phenomenon The research method used is descriptive qualitative with data collection techniques including observation, interviews, and documentation studies. The samples used in this article are students of UPTD SD Negeri 122348 Pematangsiantar and SD Swasta Taman Asuhan Pematangsiantar. Research results show that bullying can occur in various forms, including verbal, physical and nonverbal. Many students in elementary school experience or witness incidents of bullying, which can cause serious psychological impacts. Factors such as students' socio-economic background also influence the high number of bullying cases in schools. Bullying behavior can have a negative impact on the social aspects of students in elementary schools. Efforts to prevent and handle bullying in elementary schools need to involve collaboration between schools and parents. Most of the references used in research are primary literature and are up to date.